Study of tourist perception towards façade design: case study of Geographer Café, Melaka / Anuar Zahin Jasmi @ Jasni and Farid Al Hakeem Yuserrie - Jasmi @ Jasni, Anuar Zahin; Yuserrie, Farid Al Hakeem (2018)
Historic buildings that are still standing today give a perspective to people of the greatness and marvelous architecture in terms of building techniques from the days of the past. Historic buildings are in fact artifact that that give sense of place, thought and nostalgia. It also makes people curious to know more about people and culture created by the historic building itself. So, it is important to know and acknowledge the past. This study is focused on the impact of facade towards tourism in the future. The methodology used were through investigation and discussion with the conservation architect. The conservation of shop houses is addressed to trace memories of the past, present and adapt for the future condition in those places. The future Melaka shop house will become a place which tells the area's history with its physical environment, and serves the needs of the residents' social and cultural activities. The objective of the research is to know the interest of tourist on façade. The study will also help owners of shop houses to identify what factors make a shop house attractive to tourists which can have an effect on tourism in Melaka.